Partes Concerts of the 1730s–1740s from the Kyiv Collection: New Assets - Ignatenko, Yevgeniya (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
Relevance and current status of research. The Kyiv collection of partes music, which is kept in the Institute of Manuscript of V. Ι. Vernadsky National Library of Ukraine, is the largest in Ukraine. It includes about 700 choral works, and only a few dozen of them have been decoded, edited and published. In 2020, within the Musica sacra Ukraina project the author of this article decoded and prepared for performance three new partes concerts from the Kyiv collection. These are twelve-part anonymous concerts of the 1730 s – 40 s “The troubles of my heart”, “O sing unto the Lord a new song” and “Come, o people”. The purpose of the study is to describe the Kyiv partes collection and the current status of its research; to outline the main steps of working with partes manuscripts: deciphering, score compiling and editing; to present deciphered concerts in the context of current research problems of European baroque music, such as the aesthetics of oddity, as well as musical symbolism and rhetoric, which allow us to reveal the inextricable connection between the verbal and musical text of the works. Methodological framework. The work is based on proven methodologies of decoding and scientific editing of handwritten musical text, and methods of musical theoretical analysis are also used. Results and scientific novelty of the work. Three anonymous twelve-part partes concerts of the 1730 s –1740 s from the Kyiv collection “The troubles of my heart”, “O sing unto the Lord a new song” and “Come, o people” were deciphered, edited and analyzed. A comprehensive approach to studying Ukrainian baroque music is presented. It involves deciphering, editing (preparation for performance) and musicological interpretation of the work. The proposed musicological analysis, which is based on modern approaches to the analysis of baroque music, updates the European context of the Ukrainian baroque heritage